High Fidelity Spatial Light Modulator Configuration for Photo-Stimulation - Aghayee, Samira; Weikert, Mitchell; Alvarez, Phillip; Frank, Gabriel A.; Losert, Wolfgang (Frontiers in Physics, 2021)
For their capacity to shape optical wavefronts in real time into any desired illumination pattern, phase-only Spatial Light Modulators (SLM) have proven to be powerful tools for optical trapping and micromanipulation applications. SLMs are also becoming increasingly utilized in selective photo-stimulation of groups of neurons in the brain. However, conventional SLM based wavefront modulation introduces artifacts that are particularly detrimental for photo-stimulation applications. The primary issue is the unmodulated light that travels along the 0th order of diffraction. This portion of light is commonly blocked at the center of the object plane, which prevents photo-stimulation in the blocked region. We demonstrate a virtual lens configuration that moves the 1st order diffraction with the desired illumination pattern into the Fourier plane of the 0th order light. This virtual lens setup makes the whole field of view accessible for photo-stimulation and eliminates the need for removing the 0th order light in two-photon applications. Furthermore, in an example application to reconstruct a pattern consisting of an array of points, the virtual lens configuration increases the uniformity of the intensities these points. Moreover, diffraction-induced artifacts are also significantly reduced within the target plane. Therefore, our proposed high fidelity configuration yields target points with high signal to noise ratio.